The Influence of Learning Readiness and Learning Motivation on Student Achievement in MPLB Basics Subject - Septiawati, Rizka; Trisnawati, Novi (Universitas Negeri Surabaya, 2023)
This study aimed to determine how learning readiness and motivation influence student achievement in Class X MPLB (Office Management and Business Services) VHS PGRI 2 Sidoarjo. MPLB is class of office management and business services. This study used explanatory research with a random sample of 81 class X MPLB VHS PGRI 2 Sidoarjo students. The author will use quantitative descriptive data analysis as a method of data analysis. Multiple linear regression analysis was performed on the data using SPSS version 26. Readiness to learn can be said to be substantial because the findings of the data analysis show an acceptable value of 0.000 (H1), learning motivation has a considerable influence on learning achievement, as evidenced by the results of data analysis which show a value of 0.000 for learning motivation so that (H2) is accepted, learning readiness and learning motivation simultaneously affect learning achievement so that (H3) is accepted, this is indicated by an R-Square value of 0.795 which indicates that learning readiness and learning motivation influence 79.5% of learning achievement.